Mechanism of vanadate-induced activation of tyrosine phosphorylation and of the respiratory burst in HL60 cells. Role of reduced oxygen metabolites. - Trudel, S (1991)
Vanadate induces phosphotyrosine accumulation and activates O2 consumption in permeabilized differentiated HL60 cells. NADPH, the substrate of the respiratory burst oxidase, was found to be necessary not only for the increased O2 consumption, but also for tyrosine phosphorylation. The effect of NADPH was not due to reduction of vanadate to vanadyl. Instead, NADPH was required for the synthesis of superoxide, which triggered the formation of peroxovanadyl [V(4+)-OO] and vanadyl hydroperoxide [V(4+)-OOH]. One or both of these species, rather than vanadate itself, appears to be responsible for phosphotyrosine accumulation and activation of the respiratory burst. Accordingly, the stimulatory effects of vanadate and NADPH were abrogated by superoxide dismutase. Moreover, phosphorylation was activated in the absence of NADPH by treatment with V(4+)-OO and/or V(4+)-OOH, generated by treatment of orthovanadate with KO2 or H2O2 respectively. The main source of the superoxide involved in the formation of V(4+)-OO and V(4+)-OOH is the NADPH oxidase. This was shown by the inhibitory effects of diphenylene iodonium and by the failure of undifferentiated cells, which lack oxidase activity, to undergo tyrosine phosphorylation when treated with vanadate and NADPH. By contrast, exogenously generated V(4+)-OO induced marked phosphorylation in the undifferentiated cells, demonstrating the presence of the appropriate tyrosine kinases and phosphatases. A good correlation was found to exist between induction of tyrosine phosphorylation and activation of the respiratory burst, suggesting a causal relationship. Therefore an amplification cycle appears to exist in cells treated with vanadate, whereby trace amounts of superoxide initiate the formation of V(4+)-OO and/or V(4+)-OOH. These peroxides promote phosphotyrosine formation, most likely by inhibition of tyrosine phosphatases. Accumulation of critical tyrosine-phosphorylated proteins then initiates a respiratory burst, with abundant production of superoxide. The newly formed superoxide catalyses the formation of additional V(4+)-OO and/or V(4+)-OOH, thereby magnifying the response. Since vanadium derivatives are ubiquitous in animal tissues, V(4+)-OO and/or V(4+)-OOH could be formed in vivo by reduced O2 metabolites, becoming potential endogenous tyrosine phosphatase inhibitors. Because of their potency, peroxides of vanadate may be useful as probes for the study of protein phosphotyrosine turnover.